Pengaruh Brand Awareness dan Online Trust terhadap Online Purchase Decision pada Tokopedia Serta Dampaknya pada Loyalitas (Studi Kasus pada Siswa SMA Negeri 1 Sei Rampah) - Rizki Wulanita Batubara; Rakhma Wati Purba; Shella Ayu Agustin (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
This study aims to determine the effect of brand awareness and online trust on online purchase decisions at Tokopedia and their impact on student loyalty at SMA Negeri 1 Sei Rampah. The research method used is quantitative research, where variables are measured using a Likert scale. The number of samples in this study were 30 students of SMA Negeri 1 Sei Rampah. Data collection techniques used in this study were document studies and questionnaires. The data analysis technique used SPSS version 25. The results showed that 1) Brand Awareness (X1) had an effect on Loyalty (Y) Tokopedia for students of SMA Negeri 1 Sei Rampah. 2) Online Trust (X2) has no significant effect on Tokopedia Loyalty (Y) for SMA Negeri 1 Sei Rampah students. 3) Brand Awareness (X1) has no effect on Online Purchase Decision (Z) Tokopedia for SMA Negeri 1 Sei Rampah students. 4) Online Trust (X2) has an effect on Online Purchase Decision (Z) Tokopedia for SMA Negeri 1 Sei Rampah students. 5) Online Purchase Decision (Z) affects Loyalty (Y) Tokopedia for SMA Negeri 1 Sei Rampah students. 6) Online Purchase Decision (Z) is not an intervening variable that influences Brand Awareness (X1) on Loyalty (Y). 7) Online Purchase Decision (Z) is an intervening variable that is able to influence the Online Trust (X2) variable on Loyalty (Y).